Export fluctuation and overcapacity in China's manufacturing industry: The inspection of the causes of excess capacity from the perspective of external demand - Hang Liu; Ping Li; Danhui Yang (China Finance and Economic Review, 2017)
Background: Intuitively speaking, there is an inverse proportional relationship between exports and overcapacity, which means in export's busy season, enterprises would expand output and improve capacity utilization rate but control yields to avoid dull sale in slack season, causing exacerbated excess capacity. However, this is just the reflections of 'sales effect' on overcapacity by export fluctuation. For some enterprises, there is indeed 'competition effect' which may alleviate overcapacity because enterprises face even more fierce domestic competition for the sake of weak exports and may increase the utilization load of existing capacity in order to cut costs. Methods: A test is conducted in this paper to verify the relationship between export fluctuation and excess capacity based on data of China's manufacturing industry from 2001 to 2013. Results: The overall results indicate that export fluctuation is not the significant cause for excess capacity. In the small- and medium-sized enterprises or in industries with higher proportion of non-state capital, the negative relationship between exports and excess capacity is more obvious, with sales effect taking a dominant position. On the other hand, under the influence of competition effect, the relationship between the two may be positive. Conclusions: Thus, external demand shocks exert different influence on the alleviation of excess capacity of different industries, and extensively driven exports may not have anticipated effect on the dissolution of the excess capacity. To regulate overcapacity with the aid of external market, a fair and orderly competition environment should be provided to the export subjects of different size and ownerships.
Keywords: 330; Export fluctuation; Capacity utilization; Excess capacity; Manufacturing; External demand shock